2015
DOI: 10.1620/tjem.237.183
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry Improves the Therapeutic Effect of Etanercept on Patients with Juvenile Idiopathic Arthritis: Phase III Study

Abstract: Juvenile idiopathic arthritis (JIA) is the most common arthritis in the adolescents under the age of 16. Etanercept, an inhibitor of tumor necrosis factor, is often used to treat JIA despite its significant side effects. Homeopathic remedies, such as blueberries, have anti-inflammatory properties with fewer unwanted effects and should be considered as a primary treatment. We aimed to explore the efficacy and safety of combination therapy of blueberry and etanercept for JIA. Two hundred and one JIA patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
1
8
0
1
Order By: Relevance
“…300 mg kg À1 d À1 ) by rats resulted in a positive anti-inflammatory effect, as it led to a reduction in paw edema, myeloperoxidase activity (a maker for neutrophil infiltration) and formation of granulomatous tissue. Figueira et al (2016) reported that a blueberry extract caused a reduction in joint degradation in a mice model for rheumatoid arthritis in mice, results that support the observations of Zhong et al (2015) who found that blueberry juice consumption by adolescents suffering from Juvenile idiopathic arthritis (thought to be inflammatory in nature) led not only to a considerable improvement of the activity of etanercept (a known remedy) but also an amelioration of the drugs secondary effects. Ebenezer et al 2016described that the supplementation of the diet with 2% of freeze-dried blueberry powders, led to a decrease in inflammation in a post-traumatic stress disorder rat model.…”
Section: Anti-inflammatory Potentialsupporting
confidence: 65%
“…300 mg kg À1 d À1 ) by rats resulted in a positive anti-inflammatory effect, as it led to a reduction in paw edema, myeloperoxidase activity (a maker for neutrophil infiltration) and formation of granulomatous tissue. Figueira et al (2016) reported that a blueberry extract caused a reduction in joint degradation in a mice model for rheumatoid arthritis in mice, results that support the observations of Zhong et al (2015) who found that blueberry juice consumption by adolescents suffering from Juvenile idiopathic arthritis (thought to be inflammatory in nature) led not only to a considerable improvement of the activity of etanercept (a known remedy) but also an amelioration of the drugs secondary effects. Ebenezer et al 2016described that the supplementation of the diet with 2% of freeze-dried blueberry powders, led to a decrease in inflammation in a post-traumatic stress disorder rat model.…”
Section: Anti-inflammatory Potentialsupporting
confidence: 65%
“…Our study did not test whether specific foods affect RA disease activity, and we did not find a cross‐sectional association between RA disease activity scores and self‐reported change in RA symptoms from food. It is possible that certain foods on our survey do have antiinflammatory effects in RA; for example, a recent randomized trial in juvenile idiopathic arthritis tested the effect of etanercept, etanercept plus daily blueberry juice, and etanercept plus placebo juice on disease activity and circulating interleukin‐1 (IL‐1) levels . At 6 months, the etanercept plus blueberry juice group had reduced IL‐1 levels, and a significantly higher percentage of subjects achieved ACR criteria for 20%, 50%, and 70% improvement compared to the other 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled trial demonstrated that blueberry consumption decreases serum TNF‐α concentrations in postmenopausal women with pre‐ and stage 1‐hypertension . Blueberries also reduced the IL‐1α and β production and increased the level of IL‐1 antagonist in patients with juvenile idiopathic arthritis in a phase III study . Overall, pterostilbene may be a potential inflammatory suppressor as indicated by in vitro and in vivo studies.…”
Section: The Effect Of Pterostilbene On Aging Biomarkersmentioning
confidence: 98%